In Silico Genome Comparison and Distribution Analysis of Simple Sequences Repeats in Cassava - Andrea Vásquez; Camilo López (International Journal of Genomics)
We conducted a SSRs density analysis in different cassava genomic regions. The information obtained was useful to establish comparisons between cassava’s SSRs genomic distribution and those of poplar, flax, and Jatropha. In general, cassava has a low SSR density (~50 SSRs/Mbp) and has a high proportion of pentanucleotides, (24,2 SSRs/Mbp). It was found that coding sequences have 15,5 SSRs/Mbp, introns have 82,3 SSRs/Mbp, 5′ UTRs have 196,1 SSRs/Mbp, and 3′ UTRs have 50,5 SSRs/Mbp. Through motif analysis of cassava’s genome SSRs, the most abundant motif was AT/AT while in intron sequences and UTRs regions it was AG/CT. In addition, in coding sequences the motif AAG/CTT was also found to occur most frequently; in fact, it is the third most used codon in cassava. Sequences containing SSRs were classified according to their functional annotation of Gene Ontology categories. The identified SSRs here may be a valuable addition for genetic mapping and future studies in phylogenetic analyses and genomic evolution.